Les frontières latino-américaines, trajectoires historiques et construits politiques en mutation - Lucile Médina; Emmanuelle Perez-Tisserant (Caravelle, 2024)
At once geopolitical fault lines, historical scars and economic and cultural interfaces, Latin American borders share the fact of having gone through the same major historical phases since colonization –first, the emergence of nascent networks, then the formation of independent states. Today, they are still subject to political, economic and social dynamics that put them to the test and contribute to a deconstruction/reconstruction of the border as a concept, the analysis of which is stimulating for researchers in many different disciplines.